PLASIARISM IN HIGHER EDUCATION: CAUSES, CONSEQUENCES, AND PREVENTION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This research investigates the growing presence of plagiarism in high education institutions and examines some of the underlying causes that have contributed to this issue. It will also identify some of the negative consequences associated with plagiarism as it pertains to the academic integrity of scholars within higher education institutions. Numerous validated sources/analyses and comparative techniques are utilized within this study to fully evaluate the both the contemporary and digital forms of the plagiarism problem. Ultimately, the results of this study indicate that lack of time and poor knowledge of citation rules are two key reasons that have contributed to the increase of plagiarism within higher education context for students. Finally, the results of this research will provide recommendations for preventing and/or ensuring the academic integrity of students and preventing future occurrences of academic dishonesty.
Keywords: higher education, plagiarism, academic integrity, citation, copyright, paraphrase.